Heat Transfer Experiment: Top-Down Spray Type Direct Evaporative Cooler. - Berthoty, Erik; Siahpush, Ali Syyed (Journal of the Utah Academy of Sciences, Arts & Letters, 2025)
This project was a continuation of the downdraft evaporative cooler that was designed at Southern Utah University. The purpose of this research was to improve upon the existing design of the direct evaporative cooler by simplifying the heating system within the cooler, as well as exploring different water droplet sizes and their cooling performance. The relative humidity and dry bulb temperatures at the inlet and outlet of the cooler were measured when evaluating the performance of the evaporative cooler. Psychrometric charts and equations were used to predict the necessary flow rate of the water to yield a reasonable cooling performance while keeping the relative humidity close to the comfortable range of 30%-60%. It was determined that a nozzle configuration comprised of 2 parallel nozzles performed well. It cooled the air from 35.6°C to a temperature of 22.9°C with a relative humidity of 63.3%.